MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PRAKTIKUM AKUNTANSI LEMBAGA DAN INSTANSI PEMERINTAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT - Diana Sinta (Jurnal Lingkar Mutu Pendidikan, 2023)
Learning outcomes are one of the measures of success for every student in carrying out learning activities. This is one of the reasons to make efforts to improve students' learning outcomes in learning activities. This study aims to improve students' learning outcomes in the subject of Accounting Practicum for Institutional and Government Agencies. The research subjects were students in class XI Accounting 2 of SMKN 15 Jakarta, applying the cooperative learning model of Teams Games Tournament in the era of distance learning transition after the COVID-19 pandemic. The research used the action research method, conducted in two cycles, where each cycle consisted of four stages: action planning, action implementation, observation and reflection, and evaluation. The implementation activities were carried out for 3 months in the even semester of the 2021/2022 academic year. The data obtained were in the form of questionnaire results on the level of student engagement, formative test results, and observation sheets of activities. Data analysis techniques used both qualitative and quantitative methods. Based on the research results, the data showed an increase in the average student grades of about 14.09% from 68.58% in cycle 1 to 82.88% in cycle 2. In terms of students' learning completeness, there was a 50% increase where in cycle 1 only 50% of students achieved learning completeness, while in cycle 2, it was found that 100% of students met the criteria for learning completeness. The research results indicate that the use of the cooperative learning model of Teams Games Tournament can improve students' learning outcomes in the subject of Accounting Practicum for Institutional and Government Agencies.